2019
DOI: 10.1038/s41467-019-09809-3
|View full text |Cite
|
Sign up to set email alerts
|

The glycosylation design space for recombinant lysosomal replacement enzymes produced in CHO cells

Abstract: Lysosomal replacement enzymes are essential therapeutic options for rare congenital lysosomal enzyme deficiencies, but enzymes in clinical use are only partially effective due to short circulatory half-life and inefficient biodistribution. Replacement enzymes are primarily taken up by cell surface glycan receptors, and glycan structures influence uptake, biodistribution, and circulation time. It has not been possible to design and systematically study effects of different glycan features. Here we present a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 71 publications
3
81
0
Order By: Relevance
“…Given that high mannose is a precursor in the N -glycan pathway, a question that arises is whether high mannose could act as an independent signal without impacting complex N -glycan levels. Recent studies have shown that the trimming mannosidases, MAN1A1 and MAN1A2, can be independently deleted without impacting complex N -glycans ( 29 , 30 ). In addition, both enzymes are predicted to be highly regulated by miRNA ( 31 ), and miRNA downregulating MAN1A2 increased high mannose without decreasing core fucose, a marker of complex N -glycans ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that high mannose is a precursor in the N -glycan pathway, a question that arises is whether high mannose could act as an independent signal without impacting complex N -glycan levels. Recent studies have shown that the trimming mannosidases, MAN1A1 and MAN1A2, can be independently deleted without impacting complex N -glycans ( 29 , 30 ). In addition, both enzymes are predicted to be highly regulated by miRNA ( 31 ), and miRNA downregulating MAN1A2 increased high mannose without decreasing core fucose, a marker of complex N -glycans ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dramatically lowered HCP ppm values during purification of a mAb will facilitate downstream processes. These HCP-reduced knockouts can be combined with additional advantageous genetic modifications, such as the production of glycoengineered proteins [15][16][17][18] , higher viability during long culture times 19 , viral resistance or elimination [20][21][22] , and/or clones with higher protein production stability of mAbs 23 , to create predictable upstream and downstream processes with full control over critical process parameters.…”
mentioning
confidence: 99%
“…This concept was developed and pioneered by Brady and is known as enzyme replacement therapy (ERT) (Brady, 2003;Desnick and Schuchman, 2012;Aerts and Cox, 2018). The uptake of the recombinant enzyme preparations is usually mediated by mannose receptors (MR) which are present in the surface of the targeted cells and also via mannose-6-phosphate receptors (M6PR) and the asialoglycoprotein receptor (Ashwell-Morell receptor; AMR) (Figure 4) (Coutinho et al, 2012;Shen et al, 2016;Tian et al, 2019). Examples of such disorders and their corresponding impaired glycosidase are Gaucher disease and β-glucocerebrosidase (GBA), Fabry disease and α-galactosidase (GLA), Pompe disease and α-glucosidase (GAA) and Krabbe disease and β-galactocerebrosidase (GALC).…”
Section: Lysosomal Enzymes and Their Production In Plantsmentioning
confidence: 99%